Logicality and Regulatory Ethics: Lessons from the Bucharest Early Intervention Project - Fins, Joseph J. (The Hastings Center report, 2014)
Sometimes, researchers play by the rules yet their research still generates misgivings. Is it always enough, then, to abide by the rules and regulations for human subjects research? Or, in fact, might too close a focus on the rules blind both investigator and regulator to larger, overarching concerns? Or put more bluntly, could an emphasis on regulatory compliance lead to a misconstrual of the ethics of a research study?These questions are raised by the Bucharest Early Intervention Project, a study conducted on Romanian children who lived in orphanages in the aftermath of the notorious regime of Nicolae Ceaucescu.